Carbon monoxide signal regulates light-initiated seed germination by suppressing SOM expression. (July 2018) - Jia, Yujie; Li, Ruijing; Yang, Wenjuan; Chen, Zhen; Hu, Xiangyang
Graphical abstract: Highlights: CO enhances PHYB-dependent seed germination. CO signals represses the transcriptional level of SOM to alter downstream GA/ABA metabolism. CO recruits histone deacetylase 6 (HDA6) to repress SOM by diminishing histone H3 acetylation levels at this locus. Abstract: Light is a critical external signal for seed germination. The photoreceptor phytochrome B (PHYB) perceives light stimulation and promotes seed germination during the early phase after imbibition. SOM is a CCH-type zinc finger protein and negatively regulates PHYB-mediated seed germination by controlling downstream gibberellic acid (GA) and abscisic acid (ABA) metabolism. As a small molecular signal, carbon monoxide (CO) has been reported to regulate seed germination under environmental stress, but the underlying mechanism remains unclear. In this study, we first found that CO enhanced PHYB-dependent seed germination, and red light irradiation increased the transcriptional level of gene encoding Heme oxygenase 1(HY1) for CO production, this process required PHYB. Pharmacological and genetic analyses revealed that CO signals repressed the transcriptional level of SOM to alter downstream GA/ABA metabolism related genes expression, ultimately relieving the inhibitory effect of SOM on seed germination. Furthermore, CO signals possibly recruited histone deacetylase 6 (HDA6) to the promoter region of SOM to decrease its expression by diminishing histone H3 acetylation levels at this locus. Taken together, our results propose a novel mechanism for CO signals in promoting light-initiated seed germination via recruiting HDA6 to epigenetically regulate SOM expression.